LENGTH-WEIGHT RELATIONSHIP, GROWTH PATTERN AND CONDITION OF MIDAS CICHLID FISH (AMPHILOPHUS CITRINELLUS) IN LAKE BATUR, BANGLI REGENCY, BALI - Putu Tegar Wiguna Putra; Ayu Putu Wiweka Krisna Dewi, Nyoman Dati Pertami (Adisam Publisher, 2025)
Midas cichlid fish (Amphilophus citrinellus) is often referred to as a pest fish because it is a fish that can only prey but does not produce sufficient economic value, because it reproduces very quickly. This research aims to determine the length-weight relationship, growth patterns and condition of Midas cichlid fish as well as the water conditions of Lake Batur. The research was carried out using quantitative descriptive methods, with a purposive sampling method for sampling. The sampling locations were at three stations. The fishing gear used is gill nets. The total number of fish caught during data collection was 287 individuals. Based on the results of the analysis of the length-weight relationship of midas cichlid fish (Amphilophus citrinellus) in Lake Batur, the equation W=0.0215L2.92 was obtained, where from this equation the value b = 2.92 was obtained. The t test was carried out and it was found that the b value was <3 so it could be concluded that the growth pattern was negative allometric. The relative condition (Kn) of male and female Midas cichlid fish in Lake Batur is in good condition (1.01), with a less flattened body shape (fusiform). The condition of the water parameters in Lake Batur during the research was classified as good and stable for the survival of aquatic biota, one of which was the Midas cichlid fish with a pH value of 7.1-7.5; DO 5.3-6.5 mg/L; Temperature 27.8-29.6°C and brightness 1.5-1.9 m.